Thermal Decomposition Kinetics of Samarium(III) Isothiocyanate Complexes with Schiff Base Ligands - Arora*, Kishor; Kumar Sharma, Brijesh (Asian Journal of Chemistry, 2010)
Parameters related to thermal decomposition kinetics, viz., E*, A andΔS* are computed on the basis of thermal decomposition data of thecomplexes of samarium(IlI) isothiocyanate with Schiff base ligands, viz.,4-[N-(cinnamalidene) amino] antipyrine (CAAP) and 4-[N(furfural)amino] antipyrine (FFAAP), using three different methods and it wasinferred that the values of E* are sufficiently high and positive while valuesof ΔS* are negative.